Morphology of pollen in Ferula genus (Apiaceae) - Baser, Birol; Sagiroglu, Mehmet; Dogan, Gulden; Duman, Hayri (Pensoft Publishers, 2021)
In this study, the pollen morphology of all Ferula species distributed throughout the country of Turkey was studied with light and scanning electron microscopy for the first time. The aim is to identify the pollen morphological characteristics of 23 Ferula species. The pollen is radially symmetrical, isopolar and tricolporate in all examined species. Pollen grains are prolate and perprolate with the polar axis ranging from 22.28 to 40.47 rm and the equatorial axis from 13.70 to 18.73 rm. Their polar shapes are triangular, triangular to subtriangular and circular to subcircular. Several types of exine ornamentations have been observed on pollen through the use of scanning electron microscopy. The dendrogram constructed by using Average Linkage of the examined data revealed two main groups. It was determined that some pollen characteristics are more useful for classification than others. In particular, P, E, the ratio of P/E (pollen shape) and ornamentation in the polar and equatorial views are the most valuable variables for discrimination the Ferula species.
Keywords: LM; pollen morphology; SEM; Turkey; Apiaceae; Ferula